The knowledge validation process: the fundamental value of the scientific journal - Jorge E. Gomez-Marin (Asociación Colombiana de Infectología, 2020)
This pandemic has left us great lessons regarding scientific literature and the critical evaluation of knowledge.Although important journals that are rigorous when validating knowledge, had resounding errors, the ultimate lesson is that peer review is the best system, and until now the only one, that can ensure that a research work has been carried following scientific requirements, and as it is usually stated, it is the least worse scientific work evaluation systems when compared to others